Radiofrequency Treatment of Genicular Nerves Using a Hybrid Technique - Diwan, Sandeep; Gupta, Anju; Sancheti, Parag (Journal of Nepal Health Research Council, 2024)
Background: Radiofrequency ablation of genicular nerves is recommended to ameliorate the pain of osteoarthritis of the knee. However, long-term efficacy in patients with persistent pain following total knee arthroplasty remains elusive. The current study aimed to evaluate radiofrequency ablation of genicular nerves using a hybrid technique to manage severe incapacitating pain and quality of life following surgery. Methods: This prospective, observational study included patients suffering from intractable knee pain with scores > 4 on the Numeric rating scale after 6 months of total knee arthroplasty. Therapy included radiofrequency ablation of the superior medial, lateral, and inferior medial genicular nerves using a hybrid technique. The Numeric rating scale and Oxford Knee Score for quality of life were assessed before therapy and at 1-, 3- and 6 months following treatment. Results: Average pain scores reduced from 8.4 ± 1.3 (admission) to 3.3 ± 1.4 (1 month; p= <0.001) but subsequently started to increase to 4 ± 1.2 (3 months; p = 0.58), and 5.6 ± 0.9 (6 months; p= <0.001). Average Oxford Knee Score significantly improved from 14.2 ± 5.9 (admission) to 38 ± 8.6(1 month); p= <0.001, but these too subsequently reduced to 36.4 ± 7.9 (3 months); p= 1, and 22.5 ± 12.5(6 months); p= <0.001. Conclusions: Ultrasound-guided radiofrequency ablation of genicular nerves diminishes intractable pain and disability in patients with chronic knee pain following total knee arthroplasty. Treatment is safe and effective, however, the benefit declined by 6 months. A repeat block would be necessary if the pain score worsens. Keywords: Analgesia; arthroplasty; disability; genicular nerve; knee.